Behavior of certain EU member states in debt crisis (application of game theory) - Novotný, Martin (2012)
Thesis uses game theory to explain behavior of certain states in the European sovereign-debt crisis. The goal is to find out, if those states use strategies leading to equilibrium i.e. if they maximize their expected utility. Theoretical part is based mainly on repeated games and Bayesian game. Thesis summarizes development of European sovereign-debt crisis and key economic indicators. It constructs a game model of the crisis and further analyses situation of Germany, France, Italy, Spain and Greece as players in the game. The game model is then tested on key conflict situations such as relations of France and Germany, first Greek bailout negotiations or Spanish bank bailout negotiations. The results show that chosen states do maximize their expected utility in one election period. However maximization of utility in two or more election periods is limited by the parameters of democratic election system - length of election periods and information asymmetry between voters and politicians. The costs of elimination of information asymmetry would be higher than the costs of debt crisis. So even considering the costs of debt crisis the states are in long term equilibrium.